The Effect of Local Goverment Revenue and Transfer Funds on Fiscal Capacity Ratio in Lampung Province from 2017-2022 - Fitria, Annisa; Ambya, Ambya (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to determine the effect of Regional Original Income and Transfer Fund to Fiscal Capacity Ratio in Lampung Province in 2017-2022. This study used secondary data obtained from the ministry of finance. The analysis tool used is multiple regression analysis of panel data using E-views 9. The results of the regression analysis of panel data with the selected model, the Random Effect Model (REM), showed that the free variable, namely Regional Original Income, had a positive and significant effect on the Fiscal Capacity Ratio and Transfer Fund negative and insignificant to the Fiscal Capacity Ratio. It is hoped that this research can help the government to further optimize the potential of PAD to create regional independence.